Enhanced criteria for detecting oscillations in neutral delay Emden-Fowler differential equations - Maryam Al-Kandari (Kuwait Journal of Science)
In this article, we present new oscillation criteria for a specific class of second-order differential equations known as neutral delay Emden-Fowler equations. By utilizing advanced mathematical techniques, we are able to derive conditions that are more accurate and efficient than previous methods. Furthermore, our results also simplify the process of identifying oscillations in these types of equations. Our findings have important implications for various fields such as engineering, physics and mathematics, where these equations are widely used to model dynamic systems. Additionally, We have also highlighted some illustrative examples to further demonstrate the applicability and potential of our results.